Postoperative concurrent chemotherapy and radiotherapy for high‐risk cutaneous squamous cell carcinoma of the head and neck. Issue 6 (27th June 2014) - Tanvetyanon, Tawee; Padhya, Tapan; McCaffrey, Judith; Kish, Julie A.; Deconti, Ronald C.; Trotti, Andy; Rao, Nikhil G.
Abstract Background Despite resection followed by adjuvant radiotherapy, high‐risk cutaneous squamous cell carcinomas of the head and neck region (SCCHN) often recur. Because adjuvant concurrent chemoradiation reduces recurrence among high‐risk mucosal SCCHN, we sought to understand its efficacy among high‐risk cutaneous SCCHN. Methods We conducted a retrospective cohort study of patients with cutaneous SCCHN who underwent adjuvant radiation or concurrent chemoradiation. Patients must have had stage III/IV with high‐risk features, including metastatic involvement of ≥2 lymph nodes, positive margins, or extracapsular invasion. Results There were 61 patients: 27 (44%) received adjuvant radiation and 34 (56%) received adjuvant chemoradiation. The median recurrence‐free survivals were 15.4 and 40.3 months, respectively. Adjuvant chemoradiation significantly decreased the risk of recurrence or death in a multivariable analysis: hazard ratio (HR) 0.31 (p = .01). However, a difference in overall survival was not found. Conclusion For high‐risk cutaneous SCCHN, adjuvant chemoradiation was associated with a better recurrence‐free survival than adjuvant radiation alone. © 2014 Wiley Periodicals, Inc. Head Neck 37: 840–845, 2015